2018
DOI: 10.3168/jds.2018-14373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different feed type exposure in early life on performance, rumen fermentation, and feed preference of dairy calves

Abstract: The aim of the study was to evaluate the effects of early feed exposure (EFE) to different feedstuffs in dairy calves on feed preference once fed a free-choice diet and a total mixed ration later in life. Thirty (30) female Holstein calves were randomly assigned at birth to 1 of 3 EFE treatments-concentrate only (CON), hay only (HO), and concentrate and hay (COH)-from d 2 to 56. After that, all calves were offered both concentrate and hay in different buckets from d 57 to 70 to allow them free choice between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 41 publications
5
24
0
Order By: Relevance
“…Castells et al [21] claimed that when calves were offered different forages (hay, straw, and silages, respectively) with concentrates ad libitum and separately, forage consumption was only 4-6% of the total solid feed intake. Interestingly, the proportion of hay consumed across studies seems to range from 3 to 45% of total solid feed intake [20,21,25,52,87]. The difference in the proportion of forage consumed across multiple studies may also depend upon milk feeding amounts.…”
Section: The Amount and Methods Of Milk Feedingmentioning
confidence: 99%
See 4 more Smart Citations
“…Castells et al [21] claimed that when calves were offered different forages (hay, straw, and silages, respectively) with concentrates ad libitum and separately, forage consumption was only 4-6% of the total solid feed intake. Interestingly, the proportion of hay consumed across studies seems to range from 3 to 45% of total solid feed intake [20,21,25,52,87]. The difference in the proportion of forage consumed across multiple studies may also depend upon milk feeding amounts.…”
Section: The Amount and Methods Of Milk Feedingmentioning
confidence: 99%
“…The difference in the proportion of forage consumed across multiple studies may also depend upon milk feeding amounts. In two studies feeding different amounts of milk, Castells et al [52] reported that calves consumed 3% of total solid feed as forage at a low level of milk feeding (214 L from d 0 to d 57, averaged 4 L/d, around 10% of birth body weight), while Xiao et al [52] reported a greater ratio of forage to total solid feed intake, approximately 45% when a high amount of milk was offered (376 L from d 0 to d 56, averaged 6.8 L/d, around 17% of birth body weight) [25]. Milk contains a high content of fat and sugar, which provide the energy required by the calves, and greater milk amounts might alter concentrate requirements [25].…”
Section: The Amount and Methods Of Milk Feedingmentioning
confidence: 99%
See 3 more Smart Citations